Problems of existing models of protection of computer programs in Ukraine - Піхурець, Олена Вікторівна; Тіхонова, Марія Анатоліївна (Theory and practice of jurisprudence, 2019)
The law enforcement and legislative practice of most states followed the path of protecting computer programs by copyright law. It happened because the model of copyright protection of the computer programs is cheaper and faster procedure than patent protection. Patent protection, on the other hand, requires a fairly expensive and lengthy examination of a computer program for global innovation, during which the object itself may become obsolete and unpopular with potential users. Therefore, the copyright method of protecting computer programs has received preferential recognition. But a computer program does not have its own material form and it has a dynamic nature (it can be changed quickly enough by adding or rewriting the code), besides this - any computer program is first of all some information that does not allow us to speak about this object exclusively as an object of copyright the rights. In addition, when we say that a computer program is protected by copyright, we do not put an equal sign between a computer program and, for example, a literary work. We believe that a computer program is like a literary work. And from this it follows that the model of protection offered by copyright is not quite suitable for a computer program. For example, the idea itself embodied and implemented in a computer program is not the object to copyright protection, and an external form of computer program can be rewritten by another programming language or changed by an unscrupulous user, etc. To solve such problems, the copyright model of protection of the computer programs is opposed to the model of protection of these ones by the rules of patent law. For patent law, the main criterion for the division of objects into protected and unprotected is their technical or non-technical nature. But the goal of any computer program is to control the equipment and get a certain result from it. Therefore, if we take into account this thesis, a computer program can be viewed as a technical solution, and therefore as an object of patent protection. The proposed article discusses the possibilities of protecting computer programs by patent law. Both positive and negative aspects of such protection are researched. It is concluded that in Ukraine today no conceptual, methodological and legal approaches have been developed to protect computer programs as such using the rules of patent law. But in themselves, under certain conditions, computer programs and some of their components may be the object to patent protection